Public objectives and policy instruments for improving the quality of postgraduate education in China - Tang, Erzi (Frontiers in Psychology, 2022)
This paper mainly introduces and studies public objectives and instruments in educational policies that authorities can use to improve and evaluate the quality of postgraduate cultivation in China. Under the political environment in the state, the standard for the quality of postgraduate education first includes graduate students in higher education institutions who support the leadership of the Communist Party of China (CPC), educational authorities formulate and implement policies and regulations surrounding postgraduate education under the leadership of the Party committees as well. From the political perspective, moral cultivation should become an important indicator in the evaluation of the quality of postgraduate education. Specific policy instruments including examination and admission systems, graduation requirements, and performance evaluations are designed to increase knowledge and academic skills or allow students to better perform work in their future careers. Although these policy instruments have played some roles in improving the quality of postgraduate cultivation in practice, some associated social negative phenomena also appear in the field, such as academic misconduct, excessive academic and psychological pressure of postgraduate students, etc. The moral cultivation and psychological health should be measured and assessed while evaluating the quality of postgraduate education. The public objectives surrounding the higher education in political level could provide some useful and constructive recommendations to improve the evaluation system that guides the development of postgraduate education.